2019
DOI: 10.1016/j.jesp.2019.103871
|View full text |Cite
|
Sign up to set email alerts
|

Preference for hierarchy is associated with reduced empathy and increased counter-empathy towards others, especially out-group targets

Abstract: Highlights• SDO predicted decreased empathy and increased counter-empathy in general.• Higher SDO scores were associated with greater intergroup empathy bias.• SDO scores also correlated with greater counter-empathy bias when groups competed. SOCIAL DOMINANCE ORIENTATION AND EMPATHY 3 AbstractThe capacity to empathize with others facilitates prosocial behavior. People's willingness and capacity to empathize, however, is often contingent upon the target's group membership -people are less empathic towards those… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 75 publications
3
74
0
2
Order By: Relevance
“…Previous research has shown that individuals high in SDO are especially attuned to information which signals increased competition for resources and privileges arising from disruptive social changes to the social hierarchy of status and power (e.g., Duckitt & Sibley, 2017 (Uenal, Sidanius, & van der Linden, 2020). Moreover, in line with previous research showing that individuals relatively high in SDO being highly attuned to information which signals increased competition for resources, status, and power (e.g., Duckitt & Sibley, 2017;Hudson, Sidanius, & Cikara, 2019;Sidanius et al, 2017) We tested our hypotheses in two pre-registered studies in two different national contexts (USA and UK; N = 1031). A detailed overview of our hypotheses is presented in the Supplementary Online Materials (see SOM, S-Hypotheses 1).…”
Section: Climate Change and Group-based Control And Dominancesupporting
confidence: 83%
“…Previous research has shown that individuals high in SDO are especially attuned to information which signals increased competition for resources and privileges arising from disruptive social changes to the social hierarchy of status and power (e.g., Duckitt & Sibley, 2017 (Uenal, Sidanius, & van der Linden, 2020). Moreover, in line with previous research showing that individuals relatively high in SDO being highly attuned to information which signals increased competition for resources, status, and power (e.g., Duckitt & Sibley, 2017;Hudson, Sidanius, & Cikara, 2019;Sidanius et al, 2017) We tested our hypotheses in two pre-registered studies in two different national contexts (USA and UK; N = 1031). A detailed overview of our hypotheses is presented in the Supplementary Online Materials (see SOM, S-Hypotheses 1).…”
Section: Climate Change and Group-based Control And Dominancesupporting
confidence: 83%
“…Previous evidence demonstrates that target characteristics influence the amount of empathy displayed by an observer. Specifically, earlier research has shown reduced (mostly emotional) empathy for out-group members compared with that for in-group members [25][26][27][28][29][30][31], which possibly relates to reduced moral processing mediated by the medial prefrontal cortex [32]. While suggestive, these observations call for further inspection.…”
Section: Mohsin Hamidmentioning
confidence: 89%
“…One limitation is that asking how good and bad individuals feel in response to positive and negative events cannot fully capture the constructs "empathy" and "counter-empathy." Though we did not have this data at the time we ran the stereotype study, a subsequent pilot study (N=353; Hudson, Cikara, & Sidanius, 2019) assessed negative empathy and Schadenfreude using a multi-item scale that included the "good" and "bad" items as well as how sad/sympathetic/compassionate/concerned the participant felt (for empathy; items from Stürmer, Snyder, Kropp, & Siem, 2006) and how relieved/happy/satisfied the participant felt (for Schadenfreude; items from Leach et al, 2003;). Each subscale was internally consistent: empathy alpha = 0.87; Schadenfreude alpha = 0.96.…”
Section: Emotionsmentioning
confidence: 99%